Clone wars: asexual reproduction dominates in the invasive range of Tubastraea spp. (Anthozoa: Scleractinia) in the South-Atlantic Ocean - Capel,Katia Cristina Cruz; Toonen,Robert J.; Rachid,Caio T.C.C.; Creed,Joel C.; Kitahara,Marcelo V.; Forsman,Zac; Zilberberg,Carla (PeerJ, 2017)
Although the invasive azooxanthellate corals Tubastraea coccinea and T. tagusensis are spreading quickly and outcompeting native species in the Atlantic Ocean, there is little information regarding the genetic structure and path of introduction for these species. Here we present the first data on genetic diversity and clonal structure from these two species using a new set of microsatellite markers. High proportions of clones were observed, indicating that asexual reproduction has a major role in the local population dynamics and, therefore, represents one of the main reasons for the invasion success. Although no significant population structure was found, results suggest the occurrence of multiple invasions for T. coccinea and also that both species are being transported along the coast by vectors such as oil platforms and monobouys, spreading these invasive species. In addition to the description of novel microsatellite markers, this study sheds new light into the invasive process of Tubastraea.
Keywords: Sun-coral; Clone structure; Microsatellites; Population genetics; T. coccinea; T. tagusensis